PENGARUH INTTELECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI) - B51111095, Budi Suchandra (Jurnal KIAFE, 2015)
The objectives of this research are to analyze the impact of intellectual capital on firm"™s financial performance that measured by Return On Equity (ROE). Data for this research is from financial report of food and drink industry that listed in Indonesia Stock Exchange (IDX) from 2011-2013. The model that used to measure the Intellectual Capital is model that was made by pulic, that is Value Added Capital Intellectual Coefficient (VAIC). Pulic Model Separately consist of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Sturctural Capital Value Added (STVA). In this research, Statistical Product and Service Solutions 21 (SPSS 21) was used to examine the relationship between Independent variable and dependen variable financial performance. The result of this research show : (1) Value Added Capital Employed (VACA) has a positive impact on Return On Equity. (2) Value Added Human Capital (VAHU) has a positive impact on Return On Equity. (3) Structural Capital Value Added (STVA) has a positive impact on Return On Equity. (4) VACA, VAHU and STVA has a positive impact on Return On Equity. Keyword : Intellectual capital, Return On Equity (ROE), Value Added Intellectual Coefficient (VAIC), Food And Drink Industry.